Sufficient conditions for the complementability of maximal cyclic subgroups in a finite 2-group - Kreknin, V. A.; Mel'nik, I. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We present sufficient conditions for each maximal cyclic subgroup of a finite 2-group to be complementable.